2020
DOI: 10.1093/femsre/fuaa068
|View full text |Cite
|
Sign up to set email alerts
|

Environmental fluctuations and their effects on microbial communities, populations and individuals

Abstract: From the homeostasis of human health to the cycling of Earth's elements, microbial activities underlie environmental, medical and industrial processes. These activities occur in chemical and physical landscapes that are highly dynamic and experienced by bacteria as fluctuations. In this review, we first discuss how bacteria can experience both spatial and temporal heterogeneity in their environments as temporal fluctuations of various timescales (seconds to seasons) and types (nutrient, sunlight, fluid flow, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 121 publications
(183 reference statements)
3
99
0
Order By: Relevance
“…Our work has begun to bridge this gap demonstrating how important the dynamics of CRISPR-Cas systems are to their functioning and the outcome of populations facing a threat. Further investigation into different CRISPR- Cas types and classes, fluctuating environments 70 , and conditions supporting the formation of subpopulations 71 will enhance the understanding of CRISPR-Cas dynamics on both the molecular and population scale.…”
Section: Discussionmentioning
confidence: 99%
“…Our work has begun to bridge this gap demonstrating how important the dynamics of CRISPR-Cas systems are to their functioning and the outcome of populations facing a threat. Further investigation into different CRISPR- Cas types and classes, fluctuating environments 70 , and conditions supporting the formation of subpopulations 71 will enhance the understanding of CRISPR-Cas dynamics on both the molecular and population scale.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individual size is under physiological regulatory control (Davidowitz, Roff & Nijhout 2005;Chelini, Delong & Hebets 2019) and therefore responds to changes in resource levels (Marañón et al 2013). While resource levels can vary independently of population abundance (Holt 2008;Fey, Gibert & Siepielski 2019;Nguyen, Lara-Gutiérrez & Stocker 2020), high abundance leads to crowding and increasing intra-specific competition (Gavina et al 2018). Stronger competition in turn effectively reduces resource availability at the individual level, which often results in stunted growth and smaller body sizes (e.g., (Vanni et al 2009)).…”
Section: Introductionmentioning
confidence: 99%
“…There could be a trade-off between growth rate in the exponential phase of fermentation and survival rate in the stationary phase that is following the fermentation which will result in a balance of organisms that have a different strategy [110,111]. While predicted in theory, these microbial experiments have demonstrated that such a trade-off exists [112,113].…”
Section: Fluctuating Environmental Factorsmentioning
confidence: 99%